Host Factor Nucleoporin 93 Is Involved in the Nuclear Export of Influenza Virus RNA - Furusawa, Yuri; Yamada, Shinya; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2018)
Influenza virus replication relies on the functions of host factors. In our previous study, we identified host factors involved in virus replication and began analyses of their roles in this process. In this study, we focused on Nucleoporin 93 (NUP93) and revealed its importance in influenza virus replication. NUP93 knockdown mediated by siRNAs reduced viral replication and decreased the efficiency of the early step of the viral life cycle. NUP93 did not appear to be important for virus binding, internalization, or the nuclear import of viral ribonucleoprotein (vRNP); however, in NUP93-depleted cells, viral RNA accumulated in the nucleus. These results suggest that NUP93 is required for the nuclear export of viral RNA.